Analysis of selected anthropometric parameters of 6-year-old children in Warsaw compared to the peer population in the years 1996-1999 - Elżbieta Olszewska; Piotr Tabor; Dorota Trzcińska (Pediatric Endocrinology, Diabetes and Metabolism)
Introduction: Beside the positive tendencies in somatic development seen in the population of children and adolescents in Poland (e.g. the trend of increasing body height that has continued over many years), certain unfavorable phenomena are also observed. In recent decades, disorders connected with a deficiency or excess of body mass - excessive adiposity in particular - have become important health and social problems. This poses a considerable threat for being overweight, for obesity, and for other diseases of civilization. Aim of the study: The research targeted the evaluation of selected anthropometric parameters: height-weight indices, circumferences, and skinfold thicknesses in the population of 6-year-old children in Warsaw in comparison with their peer population in 1996-1999, as well as estimation of the frequency of abnormal percentile values of the aforementioned anthropometric parameters: values below the 10th percentile and above the 90th percentile. Materials and methods: The research included a sample of 160 randomly chosen children (81 boys and 79 girls) born in 2005 who attended public and private kindergartens in Warsaw. The average age of this group was 5.71±0.28 years. The study was carried out in the first quarter of 2011. The following somatic parameters were measured: body height, body mass, chest and arm circumference, triceps, and subscapular and abdominal skinfold thickness. The height-weight indices including Rohrer’s Index and Body Mass Index (BMI) were calculated. Using a method of normalization of numerical data, the obtained measurements were compared to the measurements of the peer population (n=233) from 1996 to 1999, and the significance of differences between mean values in both groups was assessed with Student's t-tests. The percentage tables with the ranges of the below normative (<10th percentile) and above normative (>90th percentile) percentile values of the studied parameters and indices were prepared on the basis of the percentile charts that presented the anthropometric parameters of children in Warsaw 12-15 years prior to this research. Results: Results especially worth underscoring are higher skinfold thickness values for children who took part in the research compared to the peer population examined in 1996-1999. This tendency was more typical of girls than boys and was observed mostly in subscapular skinfold thickness. Some of the differences between the studied population and the control group were statistically significant (girls: triceps skinfold thickness p <0.05, subscapular skinfold thickness p <0.01, sum of 3 skinfolds p <0.05; boys: subscapular skinfold thickness p <0.01). Conclusions: During the last 12-15 years, a certain tendency for greater body fatness in 6-year-old children in Warsaw has been noticed. In the present research, the alarming symptoms that indicate the threat for being overweight and for obesity were observed on the basis of measurement of skinfold thickness. However, these symptoms were not found in the case of the analysis of selected height-weight indices. The relatively high percentages of extreme values (values below the 10th percentile and above the 90th percentile) of the analyzed parameters suggest that there are many children with a non-normative somatic build in the examined group.